Neurological manifestation of Vitamin D deficiency (Indian Journal of Case Reports, 2021)
Idiopathic intracranial hypertension, also known as pseudotumor cerebri, is a disorder with raised intracranial pressure, headache, papilledema, visual disturbances with a normal cerebrospinal fluid examination, and normal neuroimaging. It is rare in the pediatric population and may occur as a manifestation of underlying disorders. Vitamin D deficiency is a common deficiency in the pediatric age group. However, neurological manifestations are rare. Here, we present the case of a 5-year-old male child who presented with headache, vomiting, and hypertension; however, the neurological examination was normal but the neuroimaging was suggestive of pseudotumor cerebri. Appropriate investigations were done. The most likely cause of pseudotumor cerebri in this patient was the deficiency of Vitamin D. We have reported this case as pseudotumor cerebri is a rare neurological manifestation of Vitamin D deficiency.